Pengaruh Model Pembelajaran Problem Based Learning Terhadap Motivasi Belajar Siswa - Asrifa RosaKhaerunnisa; Eva Meizara Puspita Dewi; Nur Akmal (ILIN Institute Makassar, 2022)
This study aims to determine the effect of problem based learning (PBL) learning model to increase students’ learning motivation. The intervention in this study was to apply a problem based learning model to increase students' learning motivation. A total of 41 participants in this study were divided into two groups, namely 24 participants in the PBL group and 17 participants in the conventional learning group. The experimental design in this study was a pretest-posttest using a quasi-experimental design with a two-group between-subject design. The results of this study prove that the problem based learning model can increase students’ learning motivation in the PBL group compared to the conventional learning group. There is a difference in the value of motivation in the group given the problem based learning model with the group given the conventional learning model. The implication of this research refers to teachers to use problem based learning models as one of the model choices that can be used to increase learning motivation